A novel transcatheter tricuspid annuloplasty for severe tricuspid valve regurgitation via the K-clip™ system: early experience in China - Xu, Rongfeng; Chen, Lijuan; Zhang, Xiaoli; Ding, Xiuxia; Wang, Zhen; Lu, Qitong; Zhang, Xiaoguo; Ding, Jiandong; Ma, Genshan (Frontiers in Cardiovascular Medicine, 2025)
BackgroundPatients who suffer from severe tricuspid regurgitation (TR) do not undergo standard care therapy because of the high surgical risk. As a result, safer and less invasive techniques are being sought after internationally. The objective of this study was to investigate the feasibility and safety of the K-Clip™ device, a novel interventional tricuspid annuloplasty system designed for transcatheter tricuspid repair that is positioned using ultrasound technology and fluoroscopy.MethodsFour patients with severe symptomatic TR (3 with massive and 1 with torrential TR) and high surgical risk [STS score of 6.7 (5.6–11.1)] underwent tricuspid annular repair with the K-Clip™ device guided by echocardiography and fluoroscopy. Echocardiographic measurements [vena contracta width, regurgitant volume, effective regurgitant orifice area (EROA)], quality-of-life (QoL) measurements [NYHA functional class, Kansas City Cardiomyopathy Questionnaire score (KCCQ), and the 6-min walk test (6MWT)] were performed before the procedure and at the 30-day follow-up assessment.ResultsThe K-Clip™ device was successfully implanted in all four patients (2 patients with 2 clips each and 2 patients with 1 clip each). No procedural or 30-day major adverse events occurred. The TR was reduced by at least 1 grade in all patients. EROA (0.93 ± 0.40 mm2 VS 0.42 ± 0.11 mm2, p < 0.05), vena contracta width (17.95 ± 8.19 mm VS 7.48 ± 1.87 mm, p < 0.05) and regurgitant volume (97.00 ± 46.41 ml VS 43.50 ± 17.13 ml, p < 0.05) were obviously reduced at 30 days after the procedure. Significant improvements in the NYHA functional class, KCCQ score (37.58 ± 6.48 VS 58.55 ± 5.13, p < 0.01), and 6MWT (239.67 ± 31.64 m VS 402.67 ± 41.53 m, p < 0.05) outcome were observed at the 30-day follow-up visit.ConclusionsThis report on the early experience of transcatheter tricuspid repair with the K-Clip™ in China revealed notable clinical improvement, acceptable safety, and high procedural success. Larger prospective trials with extended follow-up periods are required to validate these encouraging preliminary findings and to clarify the effects of the K-Clip™ on clinical outcomes.